The role of Nrf2 in oxidative stress-induced endothelial injuries - Chen, B.; Lu, Y.; Chen, Younan; Cheng, J. (2015)
© 2015 Society for Endocrinology Printed in Great Britain. Endothelial dysfunction is an important risk factor for cardiovascular disease, and it represents the initial step in the pathogenesis of atherosclerosis. Failure to protect against oxidative stress-induced cellular damage accounts for endothelial dysfunction in the majority of pathophysiological conditions. Numerous antioxidant pathways are involved in cellular redox homeostasis, among which the nuclear factor-E2-related factor 2 (Nrf2)/Kelch-like ECH-associated protein 1 (Keap1)-antioxidant response element (ARE) signaling pathway is perhaps the most prominent. Nrf2, a transcription factor with a high sensitivity to oxidative stress, binds to AREs in the nucleus and promotes the transcription of a wide variety of antioxidant genes. Nrf2 is located in the cytoskeleton, adjacent to Keap1. Keap1 acts as an adapter for cullin 3/ring-box 1-mediated ubiquitination and degradation of Nrf2, which decreases the activity of Nrf2 under physiological conditions. Oxidative stress causes Nrf2 to dissociate from Keap1 and to subsequently translocate into the nucleus, which results in its binding to ARE and the transcription of downstream target genes. Experimental evidence has established that Nrf2-driven free radical detoxification pathways are important endogenous homeostatic mechanisms that are associated with vasoprotection in the setting of aging, atherosclerosis, hypertension, ischemia, and cardiovascular diseases. The aim of the present review is to briefly summarize the mechanisms that regulate the Nrf2/Keap1-ARE signaling pathway and the latest advances in understanding how Nrf2 protects against oxidative stress-induced endothelial injuries. Further studies regarding the precise mechanisms by which Nrf2-regulated endothelial protection occurs are necessary for determining whether Nrf2 can serve as a therapeutic target in the treatment of cardiovascular diseases.